(untitled) (Nativa, 2024)
ABSTRACT: The purpose of this research is to determine how dangerous nitrates (HHRNO3) in the drinking water of the Wana district northeast of Mosul are to human health. Where 100 water samples were taken from 10 wells across the region, between July 2022 and January 2023, to determine the average nitrate ion concentration, the average chronic nitrate ion intake, and the risk quotient (QHI) for people of varying ages. According to the study’s findings, nitrate concentrations ranged from (3.0 to 15) ppm at a rate that did not exceed (12.3 ± 0.05) ppm, which is within limits recommended by the World Health Organization, which was reflected in the NPI values to range between (-0.27 to 0.23) to classify the studied water is from the category of clean water to light polluted with nitrates. As for the effects of nitrates’ chronic daily intake (CDI) and risk factor (QHI), they fluctuated between (0.081 to 0.876) mg kg-1 daily, and (0.548 to 0.050) successively, the highest values were in infants, followed by children aged (6 to 11) years, then elderly females, with values (0.554 and 0.474) mg kg-1 daily and (0.346 and 0.296), consecutively. While the age group (16 to 18) years was the least affected by the dangers of nitrates, the chronic daily intake values and the risk quotient ranged between (0.081 to 0.330) mg kg-1 daily, and (0.050 to 0.206). Thus, the studied water is considered safe for drinking because it is within the levels recommended by the US. Environmental Protection Agency (QHI=1.0). Keywords: nitrate; NPI; HHRNO3. Possíveis riscos à saúde humana por nitratos na água potável: um estudo de caso de água subterrânea no Distrito de Wana, Norte do Iraque RESUMO: O objetivo desta pesquisa foi determinar a periculosidade para a sáude humana associado aos nitratos (HHRNO3) na água potável do distrito de Wana, a nordeste de Mosul. Foram coletadas 100 amostras de água, de 10 poços em toda a região, entre julho de 2022 e janeiro de 2023, para determinar a concentração média de íons de nitrato, a ingestão crônica média de íons de nitrato e o quociente de risco (QHI) para pessoas de várias idades. De acordo com os resultados do estudo, as concentrações de nitrato variaram de 3,0 a 15 ppm, a uma taxa que não ultrapassou 12,3±0,05 ppm, sendo considerado dentro dos limites recomendados pela Organização Mundial da Saúde. Isso refletiu nos valores do NPI entre -0,27 a 0,23, permitindo classificar a água estudada como da categoria de água limpa para poluição com nitratos. Quanto aos efeitos da ingestão diária crônica de nitratos (CDI) e fator de risco (QHI), esses indices oscilaram de 0,081 a 0,876 mg kg-1 diariamente, e de 0,548 a 0,050, respectivamente. Os maiores valores foram obtidos em lactentes, seguidos por crianças com idade de 6 a 11 anos (0,554 e 0,474 mg kg-1 diariamente) e idosos do sexo feminino (0,346 e 0,296) consecutivamente. Enquanto a faixa etária (16 a 18) anos foi a menos afetada pelos perigos dos nitratos. Os valores de ingestão diária crônica e o quociente de risco variaram de 0,081 a 0,330 mg kg-1 diariamente e de 0,050 a 0,206. Assim, a água estudada é considerada segura para consume, por estar dentro dos níveis recomendados pelos EUA, com QHI=1,0. Palavras-chave: nitrato; NPI; HHRNO3.